PENGARUH KEJELASAN SASARAN ANGGARAN,PENGENDALIAN AKUNTANSI DAN SISTEM PELAPORAN PADA AKUNTABILITAS KINERJA - Mega Cahyani, Ni Made; Utama, I Made Karya (E-Jurnal Akuntansi, 2015)
Knowing the influence of budget goal clarity, control of accounting and reporting systems with organizational commitment as a moderating variable on performance accountability in government agencies is the purpose of this research. Determination of the sample using purposive sampling method with data analysis techniques that Moderation Regression Analysis. The results of empirical studies show that there is positive and significant budget goal clarity with performance accountability government agencies, there is a positive and significant impact on performance accountability accounting controls government agencies, there is a positive and significant impact on the system performance accountability government agencies, organizational commitment but not significant negative effect does not have a significant moderating effect on the relationship between budget goal clarity with performance accountability government agencies, organizational commitment does not have a significant moderating effect on the relationship between accounting controls with performance accountability government agencies, organizational commitment not have a significant moderating effect on the relationship between performance accountability reporting system with government .
Keywords: budget clarity budget, accounting controls, reporting systems, organizational commitment, performance accountability